Conceptualizing, Measuring, and Managing Customer-Based Brand Equity - Keller, Kevin Lane (Journal of Marketing, 1993)
The author presents a conceptual model of brand equity from the perspective of the individual consumer. Customer-based brand equity is defined as the differential effect of brand knowledge on consumer response to the marketing of the brand. A brand is said to have positive (negative) customer-based brand equity when consumers react more (less) favorably to an element of the marketing mix for the brand than they do to the same marketing mix element when it is attributed to a fictitiously named or unnamed version of the product or service. Brand knowledge is conceptualized according to an associative network memory model in terms of two components, brand awareness and brand image (i.e., a set of brand associations). Customer-based brand equity occurs when the consumer is familiar with the brand and holds some favorable, strong, and unique brand associations in memory. Issues in building, measuring, and managing customer-based brand equity are discussed, as well as areas for future research.